PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR IPA TERPADU SISWA KELAS VIII SMP NEGERI 13 PEMATANGSIANTAR - Saragih, Marinta; Rajagukguk, Salome; Siboro, Thiur Dianti (Jurnal Metabio, 2024)
This study was conducted with the aim of determining the effect of learning motivation on the learning outcomes of Integrated Science students of class VIII SMP Negeri 13 Pematangsiantar, and was carried out in April - May 2022 at SMP Negeri 13 Pematangsiantar. The population was 84 people and the number of samples was 84. Data analysis was carried out using correlation tests, t tests and determination tests. From the results of the correlation test, r = 0.65 was obtained, meaning that the effect of motivation on the learning outcomes of Integrated Science students of class VIII SMP Negeri 13 Pematangsiantar in the 2021/2022 Academic Year was high. Hypothesis testing was carried out using the t-test at a significance level of α = 0.05, obtained t count (7.754) > t table (1.664) then H0 was rejected and Ha was accepted, meaning that there was a significant effect between motivation on the learning outcomes of Integrated Science students of class VIII SMP Negeri 13 Pematangsiantar in the 2020/2021 Academic Year. From the results of the determination test, the contribution of motivation to students' Integrated Science learning outcomes was 42.25%. It was concluded that there was a significant influence of motivation on the Integrated Science learning outcomes of class VIII students of SMP Negeri 13 Pematangsiantar in the 2020/2021 Academic Year.